A general allometric equation for estimating biomass in Acacia mangium plantations - Hiratsuka, M.; Toma, T.; Yamada, M.; Heriansyah, I.; Morikawa, Y. (University of the Philippines, 2004)
Acacia Mangium Willd. is one of the most important tree species grown in commercial plantation in Monsoon Asia. Recently, the need for accurate information in the biomass in plantations has become more urgent, especially since the amount of carbon sequestered in afforestation/reforestation Clean Development Mechanism (AR-CDM) projects in developing countries can be included under the Kyoto Protocol. We present here a general allometric equation for estimating aboveground biomass (AGB) of A. mangium plantations from the diameter of the trees recorded at the respectives sites. Destructive samplings were conducted in Papua New Guinea, Vietnam, and Indonesia. At each site, 4-12 trees were felled, their trunks, branches and leaves were separately weighed, and allometric models for estimating AGB was determined. A general allometric equation (A log-log model) was developed from an overall total of 26 sample trees from sampled sites. No significant differences were found between the biomass estimations derived from the site-specific and the general allometric equations. The general allometric equation may allow us to estimate AGB of A. mangium plantations in Monsoon Asia without destructive sampling.